Hyperthermia: From Diagnostic and Treatments to New Discoveries - Romero-Suarez, Sandra; Mo, Chenglin; Touchberry, Chad; Lara, Nuria; Baker, Kendra; Craig, Robin; Brotto, Leticia; Andresen, Jon; Wacker, Michael; Kaja, Simon; Abreu, Eduardo; Dillmann, Wolfgang; et al. (Recent Patents on Biotechnology, 2012)
Hyperthermia is an important approach for the treatment of several diseases. Hyperthermia is also thought to induce hypertrophy of skeletal muscles in vitro and in vivo, and has been used as a therapeutic tool for millennia. In the first part of our work, we revise several relevant patents related to the utilization of hyperthermia for the treatment and diagnostic of human diseases. In the second part, we present exciting new data on the effects of forced and natural overexpression of HSP72, using murine in vitro (muscle cells) and ex vivo (primary skeletal muscles) models. These studies help to demonstrate that hyperthermia effects are orchestrated by tight coupling between gene expression, protein function, and intracellular Ca2+ signaling pathways with a key role for calcium-induced calcium release. We hope that the review of current patents along with previous unknown information on molecular signaling pathways that underlie the hypertrophy response to hyperthermia in skeletal muscles may trigger the curiosity of scientists worldwide to explore new inventions that fully utilize hyperthermia for the treatment of muscle diseases.
Keywords: muscle function